PENGARUH PEMBERIAN CACING SUTERA DENGAN PERSENTASE YANG BERBEDA TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN LARVA IKAN BAUNG (Hemibagrus nemurus) - Solihin; T. Iskandar Johan; Agusnimar (DINAMIKA PERTANIAN, 2018)
ABSTRACT This research was conducted for 21 days starting from November 12 until December 2, 2017. Located at the Seed Fish Hall (BBI) Faculty of Agriculture, Islamic University of Riau Pekanbaru. The purpose of this research is to know the effect of silkworm with the different percentages on the survival and growth of baung larvae (H. nemurus). The method used was an experimental method using Completely Randomized Design (RAL) with 4 treatments and 3 replications namely, P1 (Giving silkworm 3%/fish weight), P2 (Giving silkworm 6%/fish weight), P3 (Giving silkworm 9%/ weight of fish) and P4 (12% silkworm/fish weight). The test fish used were larvae of 3-day-old bamboo fish with an average weight of 0.02 gr and an average length of 0,7 cm. Larva baung fish obtained from the spawning in the Seed Fish Hall (BBI) Faculty of Agriculture, Islamic University of Riau Pekanbaru. The container used is 10 liters or 10 liters capacity. From the research result, the best survival percentage on P4 is 90%, then P3 is 89%, then P2 is 87% and the lowest at P1 is 85%. The absolute and absolute highest absolute growth is found in P4 weighing 0,28 gr and length 2.13 cm, then P3 weighing 0,27 gr and length 2,10 cm, then P2 weighing 0,26 gr and the next 2,07 cm length lowest on P1 weighing 0.24 gr and length of 2,03 cm. The highest daily growth rate was also found in P4 13,81%, P3 13,57%, P2 13,32%, and the lowest in P1 was 13,05%. Keywords: Silk Worms, Survival, Growth, Baung